How Does Inclusive Leadership Curb Workers’ Emotional Exhaustion? The Mediation of Caring Ethical Climate and Psychological Safety - Li, Xintian; Peng, Peng (Frontiers in Psychology, 2022)
The COVID-19 pandemic has transformed the politics, economy, and society of the world, and has dealt the most severe blow to the hospitality industry. Meanwhile, the pandemic and government control policies have brought high psychological pressure to hospitality front-line employees, resulting in emotional exhaustion. As a part of burnout syndrome, emotional exhaustion poses a threat to employees' mental health and career sustainability. Based on COR (Conservation of resources) theory, the paper investigated the effectiveness of inclusive leadership on emotional exhaustion of hospitality front-line employees by integrating the mediation roles of ethical climate and psychological safety. The data were collected from 65 teams and 358 hospitality front-line employees working in Chinese hotel and the survey is divided into two stages with the one-month gap. This research had verified the inclusive leadership has a negative impact on emotional exhaustion both indirectly through the mediation roles of ethical climate and psychological safety. The ethical climate and psychological safety played a partial mediation role between inclusive leadership and emotional exhaustion. In theory, the findings explored the mechanism of inhibitory effect of inclusive leadership on emotional exhaustion. In practice, we provided training and correct guidance to develop inclusive leadership for hotel enterprises and resolve emotional exhaustion of hospitality front-line employees to enhance the sustainability in career.